HARGA DAN ESTIMASI NILAI EKONOMIS PAKAN CAIR YANG MENGANDUNG PERSENTASE BIJI ASAM BERBEDA - Wea, Redempta; Ninu, Andy Yumima; Koten, Bernadete Barek (JURNAL KAJIAN VETERINER, 2021)
One of the conventional feed ingredients commonly used as pig feed to reduce ration prices is tamarind seeds. However, tamarind seeds have a hard seed coat texture, therefore liquid feed is fermented by formulating it with other feed ingredients, in order to know whether the liquid feed has economic value or not. The purpose of this research is to examine the price of liquid feed containing different percentages of tamarind seeds and estimate their economic value in the form of total consumption costs and feed cost per gain. The research was using yellow corn, rice bran, soybean meal, meat and bone meal, whole tamarind seeds, and aquades. Liquid feed is formulated according to the needs of the grower phase of pigs. The research treatments were R0: Fermented liquid feed (FLF) containing 0% tamarind seeds, R10: FLF containing 10% tamarind seeds, R20: FLF containing 20% ​​tamarind seeds, and R30: FLF containing 30% tamarind seeds. The variables studied were the price of liquid feed (Rp/kg), total consumption cost (Rp/kg/e), and feed cost per gain (Rp). The data were analyzed descriptively according to the research variables. The results showed that the price of liquid feed, the total cost of consumption, and the cost of the R30 treatment feed were Rp. 6868/kg, Rp. 12,579,711/kg/e, and Rp. 18,177 lower or more economical than treatment R0, R10, and R20. It was concluded that the presentation of the use of tamarind seeds in liquid feed at a level of 30% was more profitable.